Experimental verification of multilevel inverter with MPPT based solar energy - Kannan, R. (Asian Research Publishing Network, 2015)
This paper concentrates on the implementation of seven level flying capacitor multilevel inverter (FCMLI), focusing on the reduction of total harmonic distortion (THD) in a proposed type of inverter with the help of closed loop control scheme. Among the various types of multilevel inverter (MLI) topologies, FCMLI provides more advantages. The development of closed loop model for seven level FCMLI dramatically reduces the low-order harmonics and THD. Extensive simulation has been applied to compare the performance of the proposed system in closed loop control scheme with that of the open loop control scheme. In order to justify the merits of the proposed system, it is interfaced with the single phase lamp load and analyzed through simulation. This research paper is based on the approach that by tracking the load terminal voltage as the feedback thereby the closed loop scheme is designed. A prototype model for the proposed system is implemented with the single phase induction motor load whose switching is done by using ATmega16 Microcontroller and analyzed the system through hardware results. Â© 2006-2015 Asian Research Publishing Network (ARPN).